Thermally-induced arrangement of cobalt and iron in the ZIF-derived Fe, Co, Zn-N/C catalysts for the oxygen reduction reaction. (30th August 2019) - Lastovina, Tatiana; Budnyk, Andriy; Pimonova, Yulia; Bugaev, Aram; Dmitriev, Vladimir
Abstract: Heteroatom-doped carbon materials (HDCM) are perspective Pt-free alternatives for applications in fuel cells. The Fe, Co, Zn-N/C catalysts were obtained by pyrolysis (at 700 °C in Ar) of sacrificial bimetallic zeolitic imidazolate frameworks (Co, Zn-ZIF), prepared with different Co/Zn ratio by a microwave-assisted solvothermal synthesis (at 140 °C in DMF for 2 h). Co, Zn-ZIF hybrids were impregnated with a Fe II -phenanthroline complex before the pyrolysis. The structural properties of prepared materials were assessed primarily by X-ray diffraction (XRD) and transmission electron microscopy (TEM), while X-ray fluorescence (XRF) and the scanning transmission electron microscopy with energy-dispersive X-ray spectroscopy (STEM-EDS) mapping and were used for the elemental content analysis. Because in the obtained HDCM both Fe and Co participate in formation of the bamboo-like structures, synchrotron-based X-ray absorption spectroscopy (XAS) studies were performed at their K -edges. The results of in situ XAS measurements during carbonization of Fe, Co, Zn-ZIF upon heating (up to 500 °C in Ar) as well as operando XAS measurements during the electrochemical cycling of HDCM are reported. The registered changes in the oxidative state of Fe and Co (XANES) and in their coordinative environment (EXAFS) were analyzed. The study is complemented by the electrochemical tests of the synthesized HDCM (in 0.1 M HClO4 solution) towards the oxygen reduction reaction, demonstrating their high efficiency and stability in acidic medium. Graphical abstract: Image 1 Highlights: Four Co, Zn-Fe-N/C catalysts were prepared from ZIFs with different Co/Zn ratios. The changes in oxidation state of Co and Fe sites were monitored by in situ XAS. The quantity of bamboo-shaped carbon nanotubes was correlating with cobalt content. The Co/Zn = 2 composition was the most active and stable in ORR. Catalyst with optimal composition was studied by in operando XAS during ORR.